2010
DOI: 10.1677/erc-09-0253
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of prolactin and estrogens in breast cancer: resistance to chemotherapy

Abstract: Resistance to chemotherapy is a major complication in the treatment of advanced breast cancer. Estrogens and prolactin (PRL) are implicated in the pathogenesis of breast cancer but their roles in chemoresistance have been overlooked. A common feature to the two hormones is activation of their receptors by diverse compounds, which mimic or antagonize their actions. The PRL receptor is activated by lactogens (PRL, GH, or placental lactogen) originating from the pituitary, breast, adipose tissue, or the placenta.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 125 publications
2
43
0
Order By: Relevance
“…In agreement with the results in this study, some reports have suggested that cisplatin resistance on MCF-7 involves antiapoptotic mechanisms, demonstrated by a decrease of DNA-damage effector proteins, which is strongly related to the ability of the resistant cells to tolerate and repair the DNA damage due to cisplatin activity. 5,6,18 In this present study, we demonstrated that in comparison to its parental cell line MCF-7, MCF-7/CisR demonstrated several observable morphological changes. Parental cell line MCF-7 exhibited a regular spindle shape with a smooth cell membrane border, while the resistant cells demonstrated an irregular and spherical shape where some parts or the cell border are unclear (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In agreement with the results in this study, some reports have suggested that cisplatin resistance on MCF-7 involves antiapoptotic mechanisms, demonstrated by a decrease of DNA-damage effector proteins, which is strongly related to the ability of the resistant cells to tolerate and repair the DNA damage due to cisplatin activity. 5,6,18 In this present study, we demonstrated that in comparison to its parental cell line MCF-7, MCF-7/CisR demonstrated several observable morphological changes. Parental cell line MCF-7 exhibited a regular spindle shape with a smooth cell membrane border, while the resistant cells demonstrated an irregular and spherical shape where some parts or the cell border are unclear (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…It has been proposed that PRL may promote mammary tumor initiation via the JAK2/STAT5 signaling pathway, but as this cascade also maintains cell differentiation, it may also contribute to suppress invasive characteristics (Nevalainen et al 2004, Wagner & Rui 2008, Tran et al 2010. Otherwise, the concept is emerging that PRL could favor cell motility and confer resistance to chemotherapy, and thereby contribute to metastasis dissemination (for reviews Clevenger et al (2003) and Lapensee & Ben Jonathan (2010)). Such diverse effects may be mediated by distinct signaling cascades.…”
Section: Novel Viewsmentioning
confidence: 99%
“…Since incurable cancer, which afflicts over 450 persons per 100,000 annually, is a growing health epidemic, it is important to establish a relationship between environmental xenogens (i.e., endocrine disruptors) and cancer (30). Indeed, recent studies on this subject indicate a growing correlation between high exposure to endocrine disruptors (e.g., bisphenol A, xenoestrogens, polycyclic aromatic hydrocarbons) and cancer risk or drug response (13,(31)(32)(33)(34)(35)(36)(37). The question is particularly relevant given that recent developments in cancer drug therapy (e.g., targeted therapy) are markedly improving survivability.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, over the last several decades, our burden of environmental xenotoxins has increased substantially. Recent work implicates several xenogens in cancer cell growth and drug resistance (13,(31)(32)(33)(34)(35)(36)(37). Indeed, the molecular pathways governing the tissue-specific phenotypes mediated by chronic exposure to endocrine disruptors are varied, and it is clear that some important effects are mediated via nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%